2016
DOI: 10.1063/1.4948588
|View full text |Cite
|
Sign up to set email alerts
|

Broad electrical tuning of plasmonic nanoantennas at visible frequencies

Abstract: We report an experimental demonstration of electrical tuning of plasmon resonances of optical nanopatch antennas over a wide wavelength range. The antennas consist of silver nanocubes separated from a gold film by a thin 8 nm polyelectrolyte spacer layer. By using ionic liquid and indium tin oxide coated glass as a top electrode, we demonstrate dynamic and reversible tuning of the plasmon resonance over 100 nm in the visible wavelength range using low applied voltages between −3.0 V and 2.8 V. The electrical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…6a, ) and better colour tuning ( ). Due to the high local field enhancements in the gap, a small change in the properties of the material in this region, such as index of refraction or thickness, results in a large change in plasmon resonance, useful for real-time reconfigurable structures [105][106][107] or sensing 108 . In this way large area sub-μs colour changing wallpapers 109 (FIG.…”
Section: Applications and New Directionsmentioning
confidence: 99%
“…6a, ) and better colour tuning ( ). Due to the high local field enhancements in the gap, a small change in the properties of the material in this region, such as index of refraction or thickness, results in a large change in plasmon resonance, useful for real-time reconfigurable structures [105][106][107] or sensing 108 . In this way large area sub-μs colour changing wallpapers 109 (FIG.…”
Section: Applications and New Directionsmentioning
confidence: 99%
“…The size of the metallic planes as well as the distance that separates them are directly linked to the resonance wavelengths of the system, thus linked to the absorption wavelengths of the antenna array. Several designs exist : nanorods (figure 7a), which geometry is isotropic in one The dielectric thin film can be deposited using dip-coating methods [43] but self-assembly processes can also be implemented. Lin et al [42], for instance, have shown impressive assembly of controled nanoparticle assembly on metallic substrates as well as on other nanoparticle shapes, thanks to the complementarity of two DNA strands.…”
Section: Patch Antennas Made Using Lithographymentioning
confidence: 99%
“…A concerted and interdisciplinary effort has been devoted to the development of active systems in realization of postfabrication dynamic reconfigurability in a fully reversible and repeatable, fast, and ideally programmable manner. Until now, a variety of schemes have been proposed and developed in pursuit of in situ active control by electrical [153][154][155], chemical [156][157][158][159], optical [160], thermal [161], or mechanical [162][163][164] [165], tunable flat lenses [166], holograms [167], dynamic switches [66], interferometry photonic platforms [168], neural activity tracking [10,69], and information encryption [169]. Physical mechanisms behind these active plasmonic devices can be understood using lumped optical nanocircuit theory.…”
Section: Reconfigurable Plasmonic Nanoantennamentioning
confidence: 99%